Plasma Antenna with Ethernet Over Ac Power (EOP) for Wi-Fi Application - Hilmi, M.; T.Ali, M.; Jaafar, H. (International Journal of Engineering and Technology, 2018)
This paper proposed a plasma antenna using a fluorescent tube that contain a mixture of Argon gas and mercury vapor. The objective of this project is to carry Ethernet from service provider by integrating the plasma antenna with AC power line so that the antenna could transmit Wi-Fi signal at many locations simultaneously. The length of the antenna tube is 586 mm and 24.3 mm in diameter. The antenna has been simulated using Computer Simulation Technology (CST) and was integrated with a router and Ethernet over power line (EoP) device. Return loss, Wi-Fi strength and signal strength were calculated and measured. The antenna is designed to operate at 2.4GHz for Wi-Fi application.